Pengaruh Pemberian KUR dan Strategi Pemasaran terhadap Kemampuan Bertahan UMKM di Tengah Pandemi Covid-19 (Studi Kasus UMKM di Kota Denpasar) - Ni Luh Putu Yesy Anggreni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
One of the government's efforts to help the sustainability of MSMEs in the midst of the Covid-19 pandemic is to provide KUR, this effort to stimulate MSMEs in developing their businesses. The objectives of this study were to determine: (1) the effect of giving KUR on the survival capacity of MSMEs in the midst of the Covid-19 pandemic; (2) The Influence of Marketing Strategy on the Survival Capability of MSMEs in the Middle of the Covid-19 Pandemic; (3) The Effect of Giving KUR and Marketing Strategy together on the Ability to Survive MSMEs in the Middle of the Covid-19 Pandemic. Data were analyzed by statistical simple regression analysis and multiple regression of two predictors. Through the results of predictions with predictors X1 (Giving KUR) and X2 (Marketing Strategy) to Y (Ability to Endure), the Freg price is 138.32. With (Nm-1) in this case db = 107/2, with a significance level of 5%, the value of Ftable is 3.08 This means that the regression line analyzed is significant to be used as a basis for predictions because it is between the criteria (Y) and the predictors (X1 , X2) there is a significant relationship. Freg is greater than the value of F table or 138.32> 3.08. So that the Zero Hypothesis tested is rejected and the Alternative Hypothesis is accepted which indicates that there is a significant relationship between KUR and Marketing Strategies on the Ability to Survive for MSMEs in the Middle of the Covid-19 Pandemic (Case Study of MSMEs in Denpasar City). Relative Contribution (SR%) for each predictor, namely X1 (giving KUR) = 70.21%, and X2 (Marketing Strategy) = 29.78%. While the regression line is 53.67% which consists of the effective contribution of predictor X1 (giving KUR) = 37.69%. And the effective contribution of predictor X2 (Marketing Strategy) = 15.98% while the remaining 46.33%.% Is influenced by other factors. Based on the results of the analysis and conclusions, it is hoped that MSME actors will further improve their marketing strategies so that they can compete in accordance with the current situation and conditions. Keywords: KUR; Marketing strategy; Ability to Endure